2012
DOI: 10.1021/jf303595e
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Acylation of Isoorientin and Isovitexin from Bamboo-Leaf Extracts with Fatty Acids and Antiradical Activity of the Acylated Derivatives

Abstract: This study enzymatically acrylates two flavonoids from bamboo-leaf extracts, isoorientin and isovitexin, with different fatty acids as acyl donors using Candida antarctica lipase B (CALB). The conversion yield ranged from 35 to 80% for fatty acids with different chain lengths. Higher isoorientin and isovitexin conversion yields (>75%) were obtained using lauric acid in tert-amyl-alcohol as the reaction medium. (1)H and (13)C nuclear magnetic resonance spectroscopy analysis showed that, in the presence of CAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 37 publications
12
40
0
1
Order By: Relevance
“…activated molecular sieves (30-150 g/l) were also employed for water removal in order to drive the reaction toward biosynthesis. Reactions were incubated at 60 °C with agitation (210 rpm) for 48 h [9,12,14]. Reaction bioconversion was monitored by HPlC to confirm production, with bioconversion (%) calculated following HPlC analysis as the area of the ester product divided by the total isoorientin and its ester area, multiplied by 100.…”
Section: Isolation Of Isoorientinmentioning
confidence: 99%
See 1 more Smart Citation
“…activated molecular sieves (30-150 g/l) were also employed for water removal in order to drive the reaction toward biosynthesis. Reactions were incubated at 60 °C with agitation (210 rpm) for 48 h [9,12,14]. Reaction bioconversion was monitored by HPlC to confirm production, with bioconversion (%) calculated following HPlC analysis as the area of the ester product divided by the total isoorientin and its ester area, multiplied by 100.…”
Section: Isolation Of Isoorientinmentioning
confidence: 99%
“…The injection volume was 20 μl, while the column temperature was maintained at 30 °C. Different compounds were quantified at 330 nm with the UV detector [14].…”
Section: Purification Of Ester Productsmentioning
confidence: 99%
“…在黄酮类化合物改性中, 常用的方法有生物催 化 [11,12] 和化学催化 [13,14] . 相比于化学方法修饰, 酶催化 改性的方法具有反应条件温和、选择性高、操作简单等 特点, 特别是对于多官能团的黄酮类天然产物改性而 言, 酶催化因具有高的区域选择性和立体选择性而具有 明显优势 [15] .…”
Section: 强的抑制活性unclassified
“…"Patriot," we used this compound A c c e p t e d M a n u s c r i p t 6 as the reaction subject. Maused lauric and tetradecanoic acids to acylate bamboo leaf flavonoid and found that lauric acid showed better effects on glucoside in an acylation reaction [29] . Thus, we selected lauric acid as the acylating agent.…”
Section: Introductionmentioning
confidence: 99%